Global Times’ Framing for China’s Noopolitics in the South China Sea - Maulaya, Mahbi; Wafi, Fadhlil (International Journal of Media and Communication Research, 2023)
The South China Sea (SCS) is an area of water endowed with rich natural resources and a strategic location for geopolitical interests. As the consequence, China has put the SCS in its list of the Great Rejuvenation Goals. China's modus operandi to attain its SCS ambition has been various in the way. It ranges from making land reclamation and artificial islands, sending citizens to artificial islands and further applying its jurisdiction and administration, conducting military activities, and wielding diplomacy efforts. Another path China undergoes to manifest its maritime empire in the SCS is media framing. This study highlights how China employs Global Times, its state-owned media, to construct the mind frame that the SCS belongs to China. To achieve the objective of the study, this paper use Zhongdang Pan and M Kosicky's framing analysis to identify Global Times' type of framing and qualitative method to seek the intention of the frame. This paper finds that Global Times assist the Chinese government in claiming the SCS by syntactic and rhetorical framing; dominantly quoting pro-China experts/academics/statesman, emphasising 'sovereignty' words and displaying a narration that the SCS belongs to China, using Chinese to name the islands in the SCS, and echoing 'no conflict in the SCS' rhetoric. This study proves that China is also pursuing its South China Sea Dream by exercising noopolitics.